The Impact of Health Education through Lecture-Discussion Methods on Enhancing Hepatitis B Knowledge - Diniarti, Fiya; Said, Mohamed Saifulaman Mohamed; Rashid, Norhashima Abd (Qualitative and Quantitative Research Center, 2023)
Health education is essential in promoting awareness and reducing stigma related to various medical conditions. Health education for pregnant women is vital to increase their knowledge about various aspects of health, including hepatitis B. Health education using the lecture-discussion method effectively conveys medical information and facilitates participants’ more profound understanding. This study aims to determine the influence of health education using the lecture-discussion method on knowledge about hepatitis B infection in pregnant women. This study uses pre-experimental research. Data analysis used univariate and bivariate analysis, and the number of samples was 144 respondents. The results show a significant influence of health education with lecture and discussion methods on pregnant women’s knowledge about hepatitis B infection. Health education, which integrates lectures and discussions, is hoped to be carried out continuously and sustainably to increase knowledge about hepatitis B infection in pregnant women. The researcher’s recommendation in the future is to provide health education with a combination method integration (video, lecture, and discussion) in control groups and interventions. This research contributes to providing information and assisting in designing more effective health education interventions.